ENCAPSULATED BAITS CONTAINING ZINC SULFATE AND Trichoderma harzianum REDUCE FUNGAL GARDEN IN Atta sexdens COLONIES - da Silva, Daniella Gonçalves; Lucena Júnior, Aldemir; Sarmento, Renato de Almeida; Santos Silva, Cynthia Lhourrana; Teles Tenório, Amanda Caroline; de Souza, Danival José; Melo, Márcio Silva (REVISTA DE AGRICULTURA NEOTROPICAL, 2020)
The aim of the study was to test the effects of various concentrations of zinc sulfate (ZnSO4) on the radial growth of Trichoderma harzianum and Leucoagaricus gongylophorus in Petri dishes. In addition, we investigated the acceptance of baits containing live propagules of the encapsulated T. harzianum fungus and baits containing ZnSO4 by foraging leafcutter worker ants, A. sexdens, as well as their effects on the colonies of these ants. For the in vitro test, the design was completely randomized using ten replicates of a 2 × 7 factorial scheme: two species of fungi (T. harzianum and L. gongylophorus) and seven concentrations of ZnSO4. For bait acceptance tests, four treatments were used: baits without the mycelium and ZnSO4 (T1, control), baits containing encapsulated T. harzianum mycelium (T2), baits containing ZnSO4 (T3), and baits containing zinc sulfate and the encapsulated T. harzianum (T4). Each treatment was tested in duplicates using eight colonies. In the in vitro test, a ZnSO4 concentration of 0.25 g/L was sufficient to completely inhibit the development of L. gongylophorus without affecting the development of T. harzianum. In the bait acceptance test, the workers accepted 55% of the bait combination of ZnSO4 and T. harzianum. This suggests the potential of treatment T4 in controlling leafcutter ants. Moreover, treatment T4 is environmentally friendly.